INTERFERENSI BAHASA MAKASSAR TERHADAP PENGGUNAAN BAHASA INDONESIA DALAM APLIKASI WHATSAPP TINJAUAN:MORFOSINTAKSIS - Dian Angreani; Asriani Abbas; Kaharuddin (Media Bina Ilmiah, 2022)
Interference is done by speakers in communicating through the Whatsapp application and unwittingly disrupts the structure of the Indonesian language. This study aims to examine the elements and factors that can affect the occurrence of Makassar language interference with Indonesian in the Whatsapp application. This type of research uses descriptive qualitative research methods with two types, namely library research and field research. The results of this study indicate that there is morphological interference and syntactic interference. The influencing factors are internal and external factors